Mechanically Adaptive Organic Transistors for Implantable Electronics. (15th April 2014) - Reeder, Jonathan; Kaltenbrunner, Martin; Ware, Taylor; Arreaga‐Salas, David; Avendano‐Bolivar, Adrian; Yokota, Tomoyuki; Inoue, Yusuke; Sekino, Masaki; Voit, Walter; Sekitani, Tsuyoshi; Someya, Takao
<x xml:space="preserve">Abstract</x> A unique form of adaptive electronics is demonstrated, which change their mechanical properties from rigid and planar to soft and compliant, in order to enable soft and conformal wrapping around 3D objects, including biological tissue. These devices feature excellent mechanical robustness and maintain initial electrical properties even after changing shape and stiffness. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>